"Jesus Was a Good Gangster": Honor and Religion in The YouTube Channel Grim Hustle - Feichtinger, Christian (Journal for religion, film and media, 2024)
In May 2022, the YouTube channel Grim Hustle launched a series of short videos containing life advice, rules for life, and motivational speeches by a "Russian mafia boss". Although the protagonist was soon identified as an actor, the channel gained more than one million followers within eighteen months of its launch. The channel’s main narrative is the call for a return to traditional values and habits, most notably honor, as an antidote to a modern, "broken" society that is dismissed as corrupting and oppressive. Traditional religion is promoted by the channel as a vital part of old values and habits. The article focuses on the representation of religion in the channel’s videos and how it is shaped by the underlying concept of honor.